A Method to Derive the Time of Onset of Infection from Serological Findings - Steimann, F.; Hayde, M. (Methods of Information in Medicine, 1997)
Among the diagnostic problems requiring a retrospective assessment of the time an event occurred is that of screening for primary infection with Toxoplasma gondii acquired during pregnancy. We suggest a method to derive the possible times of onset of infection from a small sequence of serological samples by matching them against the knowledge about possible courses of infection. Special care is taken to properly address the relative change of consecutive samples, a nontrivial problem when reasoning about sparsely sampled time courses. To investigate the practicability of our approach we conducted a retrospective and a simulated prospective evaluation based on the samples of 394 pregnancies, randomly selected from our toxoplasmosis database; we could demonstrate an overall accuracy of 95.7%.
Keywords: Temporal Reasoning; Serodiagnosis; Infection; Onset; Toxoplasma Gondii